The scientific method: the DNA of the educational research in the LOE, LOMCE and LOU - José Antonio Domínguez Montes (ADIDE Federación, 2015)
It becomes necessary to promote a model of critical, reflexive, competent, investigative professorship and with positive attitudes towards the improvement of his educational practice, impregnating to his student body and initiating it in the educational research and therefore scientific. The educational research is treated in different laws as for education such as, the Organic Law 6/2001, of December the 21st, on Universities (OLU) in his consolidated text, as well as in the Organic Law 2/2006 of May the 3rd, of Education (OLE), amended by the Law 8/2013, of December the 9th, for the Improvement of Quality in Education (OLIEQ), sharing both its preliminary Title and Title II, in this case together with experimentation and educational innovation. Defining and clarifying each of the linked concepts, and that they part with the scientific method, we will proceed to justify the authentic need to investigate in education as it comes gathered in the OLE, OLIEQ and OLU.